PERAN JEJARING PENGELOLA SAMPAH MANDIRI (JPSM) SEHATI DALAM PENINGKATAN KINERJA PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI KABUPATEN SLEMAN, YOGYAKARTA - Hijrah Purnama Putra; Rini Darmawati; Ani Sumiarti (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The quantity of waste produced continues to increase every year, along with the increase in the population in a region. However, such improvements tend not to be comparable to their management capabilities. Through Jakstrada, 100% management can be achieved by 2025, but requires high community participation in order for the target to be achieved. Yogyakarta has a high growth rate of community-based waste management activities, especially Sleman Regency which until now has had 147 locations, with various forms of activities, such as waste banks, waste alms, TPS 3R and other forms of independent waste management. However, it is recognized that the growth has not been evenly distributed at the sub-district level (kapanewon) and the village (kalurahan). Based on the analysis obtained influence from the role of Independent Waste Management Network (JPSM) Sehati Sleman Regency as the parent organization. So that mapping the location, potentials and challenges is important to do, while restructuring the parent organization in order to provide performance in the process of mentoring, coordination and liaison with various stakeholders.